Annealing effects of 850 nm vertical-cavity surface-emitting lasers after proton irradiation. Issue 9 (September 2022) - Chen, Jiawei; Li, Yudong; Maliya, Heini; Guo, Qi; Zhou, Dong; Wen, Lin
Abstract: A long-term annealing experiment was performed using 850 nm vertical-cavity surface-emitting lasers (VCSELs) irradiated with 10 MeV protons. Static parameters such as the threshold current, slope efficiency, and light output power were tested using annealing currents above and below the threshold. The experimental results indicated that these parameters gradually recovered with annealing time, and the degree of recovery was proportional to the annealing current. In addition, curve fitting was performed to obtain the direct relationship between the slope efficiency and annealing current. A comprehensive investigation of the annealing behavior of VCSELs is crucial for device applications in harsh radiation environments. Abstract : VCSEL; Displacement damage effect; Annealing; Proton radiation; Non-radiative recombination center.